The role of accounting mechanisms for corporate governance in reducing financial corruption (field study on Omdurman National Bank 2018-2020 AD) (Economic studies journal, 2021)
AbstractThe study aimed to test and know the impact of external and internal audits and audit committees in the framework Of corporate governance in reducing financial corruption, and to achieve the objectives of the study, the researcher Used the descriptive approach to know the effect of accounting mechanisms for corporate governance in reducing Financial corruption.The study reached a set of results, the most important of which are: The internal audit is located within an Organizational structure that allows the performance of its tasks in an appropriate manner, which limits financialCorruption, and the external auditor possesses scientific qualifications and high professional competence to help him Complete his mission, which limits the limits of financial corruption, and the audit committee understands the Responsibilities and duties of management in relation to accounting estimates when preparing financial reports, Which limits financial corruption?I also reached a set of recommendations, the most important of which are: the need to activate the mechanisms of Governance, provided that it includes the imposition of sanctions on economic institutions that carry out financial Corruption practices, with the aim of contributing to the reduction of those practices and with the aim of providing Transparency and objectivity, and the need to focus on the creation of mechanisms independent of the profession of Accountant and auditing the guarantee for promoting and raising the ethical behavior of this profession to reduce the Practices of financial corruption.
Keywords: corruption; financial corruption; corporate governance; governance mechanisms